Political Connections and Executive Remuneration in Indonesia: Does the Role of Institutional Ownership Matters? - Arif Wahyu Nur Kholid; Evy Rahman Utami; Etik Kresnawati (Accounting Analysis Journal, 2022)
Purpose : The study aims to examine the role of institutional ownership in moderating the effect of political connections on executive remuneration in Indonesia. Method : The study uses a quantitative method approach. The population of this study was all companies listed on the Indonesia Stock Exchange from 2015 to 2020. Research data sourced from www.idx.co.id, and OSIRIS. Using the purposive sampling method, 2,275 observations firms were determined. Hypothesis testing was carried out using multiple linear regression for panel data. Findings : The results revealed that only the main effects influenced executive remuneration. Institutional ownership, political connections positively affected executive remuneration. In addition, the interaction effect of institutional ownership was not shown to moderate the relationship between political connection and executive remuneration. These results suggest that political connection and institutional ownership are necessary to determine executive compensation. Therefore, stakeholders must be aware of the political connection misuse possibility in determining the executive compensation package. On the other hand, institutional ownership may be related to incentive-based pay, which needs to be explored further. Novelty : The novelty of this study is a new study that examines the phenomenon of political connections to executive remuneration in Indonesia and includes the role of governance-Institutional ownership as a moderating variable. In addition, this study uses the unbalance panel method, which examines all sectors of companies listed on the Indonesian stock exchange and observed for 6 periods or 2015 - 2020. Keywords: Corporate Governance; Institutional Ownership; Political Connection; Remuneration